Historiography and the formation of philosophical canons - Lapointe, Sandra; Reck, Erich H., 1959- (New York, NY : Routledge, 2023)
"This book presents a series of case studies and reflections on the historiographical assumptions, methods, and approaches that shape the way in which philosophers construct their own past. The chapters in the volume advance discussion of the methods of historians of philosophy, while at the same time illustrating the various ways in which philosophical canons come into existence, debunking the myth of analytical philosophy's ahistoricism, and providing a deeper understanding of the roles historiographical devices play in philosophical thought. More importantly, the contributors attempt to understand history of philosophy in connection with other historical and historiographical approaches: contributors engage classical history of science, sociology of knowledge, history of psychology and historiography, in dialogue with historiographical practices in philosophy more narrowly construed. Additionally, select chapters adopt a more diverse perspective, by making place for non-Western approaches and for efforts to construe new philosophical narratives that do justice to the voice of women across the centuries. Historiography and the Formation of Philosophical Canons will be of interest to researchers and advanced students working in history of philosophy, meta-philosophy, philosophy of history, historiography, intellectual history, and sociology of knowledge"--
Reimagining the canon through the lens of Mexican philosophy / Robert Eli Sanchez, Jr. -- When logic goes East (and far West) / Julie Brumberg-Chaumont -- How to change a philosophical canon / Lisa Shapiro -- History as a weapon : T.H. Green, empiricism, and the new science of mind / Alexander Klein -- The sociology of philosophical canons : the case of Georg Simmel / Martin Kusch -- Canonizing Wittgenstein : biography, English male homosocial desire, and Wittgenstein's queerness as a Cambridge Don, 1953-1977 / David Loner -- Interpretation and the history of philosophy : a pragmatic account / Jeffrey Elawani and Sandra Lapointe -- Making past thinkers speak to us through pragmatic genealogies / Matthieu Queloz -- Historical narratives and transtemporal problems in philosophy / Claude Panaccio -- Philosophy and its past : a Eudaimonistic perspective/ Aaron Preston -- Philosophical histories, dynamic practices, and contested canons / Erich H. Reck -- Let it rip : an analysis of philosophical canons and a partial argument for being a canon-shredder / Landon D.C. Elkind -- From popper to standpoint theory : reason and the canon / Lydia Patton -- Frankenstein in Athens : digital history of philosophy comes alive! / Christopher D. Green -- Separate isles? On historiography, philosophy, and intellectual history / Daniel Woolf.
Keywords: Philosophy -- Historiography; Philosophy -- History; PHILOSOPHY / History & Surveys / General; HISTORY / Historiography